Analysis of Students' Mathematical Communication Skills in Solving Space Building Problems - Dewi Ode; Dinar Riaddin; Rizal Kamsurya; Lastri Lastri; Kapraja Sangadji (Constructivism: Journal of Research in Education, 2024)
Communication skills in mathematics learning are very necessary to achieve good learning outcomes. This study aims to determine students' mathematical communication skills in completing building space material. This type of research is qualitative descriptive with the number of subjects used, namely 1 person. The chosen subject is the student who obtained the highest score. The instruments used are tests and interviews. Tests are used to select subjects and interviews are conducted to determine students' reasoning abilities. The data analysis technique used is using qualitative data analysis, namely using the stages of data collection, data presentation and conclusions. Based on the results of data analysis, it is known that AW subjects meet 7 indicators of mathematical communication skills, namely subjects are able to connect real objects, images, and diagrams into mathematical ideas, subjects can explain ideas, situations, and mathematical relations orally and in writing with real objects, images, graphs, and algebra, subjects can express everyday events in language or mathematical symbols,  subjects can listen, discuss, and write about mathematics, subjects can read with comprehension a written mathematical presentation, subjects can make conjectures, construct arguments, formulate definitions, and generalizations, and subjects can explain and make questions about mathematics that have been studied, while subject AB only meets 3 indicators out of 7 indicators used